2011
DOI: 10.1007/s00345-011-0731-y
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative positive urine cytology is a risk factor for subsequent development of bladder cancer after nephroureterectomy in patients with upper urinary tract urothelial carcinoma

Abstract: Risk factor for subsequent development of bladder cancer after NUx was preoperative positive urine cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 22 publications
(36 reference statements)
3
37
1
1
Order By: Relevance
“…Matsui et al [6], Terakawa et al [7], and Hisataki et al [12] also reported that tumor multiplicity was one of the independent risk factors for bladder recurrence. On the other hand, tumor multiplicity was not a risk factor for bladder recurrence in many other studies [8,15,16,19]. It was also not a risk factor for bladder recurrence in our study.…”
Section: Discussionmentioning
confidence: 39%
See 4 more Smart Citations
“…Matsui et al [6], Terakawa et al [7], and Hisataki et al [12] also reported that tumor multiplicity was one of the independent risk factors for bladder recurrence. On the other hand, tumor multiplicity was not a risk factor for bladder recurrence in many other studies [8,15,16,19]. It was also not a risk factor for bladder recurrence in our study.…”
Section: Discussionmentioning
confidence: 39%
“…Whereas tumor grade was significantly associated with bladder recurrence in some studies [5,8,13], it showed no such association in many other studies [4,6,7,9,12,15,16,19]. Huang et al [8] suggested that this discrepancy may be due to the differences in the grading criteria, i.e.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations